2016
DOI: 10.1186/s12889-016-3565-0
|View full text |Cite
|
Sign up to set email alerts
|

A multilevel analysis of lifestyle variations in symptoms of acute respiratory infection among young children under five in Nigeria

Abstract: BackgroundNigeria has the second highest estimated number of deaths due to acute respiratory infection (ARI) among children under five in the world. A common hypothesis is that the inequitable distribution of socioeconomic resources shapes individual lifestyles and health behaviors, which leads to poorer health, including symptoms of ARI. This study examined whether lifestyle factors are associated with ARI risk among Nigerian children aged less than 5 years, taking individual-level and contextual-level risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
52
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 35 publications
8
52
0
2
Order By: Relevance
“…Those cut-off points were selected based on prior research that have identified a high occurrence of adverse events for intervals shorter than 24 months [ 47 ]. Region is a six-level variable (North west, North east, North central, South east, South south and South west) that was included to take into account between region heterogeneity [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Those cut-off points were selected based on prior research that have identified a high occurrence of adverse events for intervals shorter than 24 months [ 47 ]. Region is a six-level variable (North west, North east, North central, South east, South south and South west) that was included to take into account between region heterogeneity [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Differential exposures of niche where a child is born and raised constitutes determinants of health outcomes [ 26 ]. Thus evidence of specific interventions effective in reducing ARI is necessary [ 27 ] for understanding the contributing factors to the inequity of ARI prevalence and examining why children from poor regions, with political problems and religious unrest in recent times leading to air pollutions, migration which may result into communities or households having higher risk of ARI [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Résumé des données relatives à l'efficacité des pratiques d'hygiène des mains dans la prévention de la grippe présumée ou confirmée en laboratoire en milieu communautaireHygiène des mains et grippeNeuf études ont évalué l'efficacité des interventions ou des pratiques d'hygiène des mains dans la prévention de la grippe présumée ou confirmée en laboratoire en milieu communautaire, dont deux ECR(13,15), une étude de cohortes(25), trois études cas témoins(19,21,26) et trois études transversales(18,20,23).Les résultats des études étaient variables; six études sur neuf ont conclu qu'une intervention ou pratique d'hygiène des mains réduisait le nombre de cas de grippe confirmée en laboratoire(21,26) ou présumée(15,18,20,23), tandis que trois études ont conclu qu'il n'y avait pas de lien statistiquement significatif entre l'hygiène des mains et une diminution des cas de grippe(13,19,25). Un des deux ECR a fait état d'un lien significatif entre le lavage des mains et une diminution du risque de syndrome grippal(15), tandis que l'autre ECR n'a relevé aucun effet d'une intervention de désinfection des mains sur le lieu de travail sur les cas de grippe cliniquement diagnostiquée auto-déclarée(13).…”
unclassified
“…Un des deux ECR a fait état d'un lien significatif entre le lavage des mains et une diminution du risque de syndrome grippal(15), tandis que l'autre ECR n'a relevé aucun effet d'une intervention de désinfection des mains sur le lieu de travail sur les cas de grippe cliniquement diagnostiquée auto-déclarée(13). Quant aux études observationnelles, fondées sur les pratiques d'hygiène des mains auto-déclarées(20,21,23,25,26) ou observées(18,19), elles ont pour la plupart fait état d'une probabilité d'infection présumée significativement inférieure sur le plan statistique(18,20,21,23,26). Il n'a pas été possible de réaliser une analyse qualitative plus détaillée des résultats étant donné le nombre limité d'études hétérogènes.…”
unclassified